Analysis of solid oxide fuel and electrolysis cells operated in a real-system environment: State-of-the-health diagnostic, failure modes, degradation mitigation and performance regeneration. (November 2022) - Subotić, Vanja; Hochenauer, Christoph
Abstract: Solid oxide cells (SOC) play a major role in strategic visions to achieve decarbonization and climate-neutrality. With its multifuel capability, this technology has received rapidly growing amount of attention from researchers worldwide. Due to the great flexibility of SOCs with respect to the fuels that can be used, not only hydrogen, but also biogas, natural gas, diesel reformates and many other conventional and alternative fuels can be used. This makes it possible to couple SOCs with diverse sustainable fuel sources to generate electricity or to generate valuable fuels such as syngas when utilizing renewable electricity. In this paper, the reader is provided with a review of the existing knowledge about solid oxide fuel cell (SOFC) and solid oxide electrolysis (SOE) systems and how to safely operate them over the long-term, placing a special focus on real-world operating environments. Both the utilization and generation of real commercially available fuels are taken into consideration. Different failure modes can appear during the system operation under real-world conditions and reduce the SOC lifetime, an aspect that is extensively discussed in this review. Firstly, a detailed discussion of the difference between carbon-free and carbon-containing fuels is presented, considering different impurities and their impacts on the SOC performance, stability and lifetime. Secondly, unfavorable operating conditions are presented and possibilities for the early identification of different failure modes are explored. An overview of available conventional and non-conventional diagnostic tools and their applications is provided here. Overall, this review paper presents a guideline for all relevant degradation issues related to SOCs operated in a real-world environment, describing (i) how these issues appear and how to understand them, (ii) how to predict them, (iii) how to identify them and (iv) how to prevent them, as well as, if required, how to reverse them. To achieve this goal, individual chapters specifically address failure modes, degradation prediction, degradation prevention and performance regeneration. The reader is provided with necessary knowledge about the long-term and short-term operating stability and the degradation provoked in a compact summary. The available knowledge about specific process frequencies is summarized in one diagram, which is a novel contribution of this review. This enables researchers to rapidly identify all occurring process mechanisms with SOFCs and SOECs. Moreover, suggestions for how to accelerate degradation and how to regenerate performance are summarized in several tables.